Inpatient Service Quality and Intention to Recommend: The Mediating Roles of Satisfaction and Loyalty at PKU Muhammadiyah Delanggu General Hospital - Fery Ardi Kurniawan; Burhannudin Ichsan; Muzakar Isa (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Patient-centered service quality influences patient satisfaction, loyalty, and intention to recommend. Objective: This study examined the effect of inpatient service quality on intention to recommend, with patient satisfaction and loyalty as mediators at RSU PKU Muhammadiyah Delanggu. Method: This quantitative study used an explanatory cross-sectional design conducted at RSU PKU Muhammadiyah Delanggu from March to April 2026. A total of 275 adult non-intensive inpatient respondents were selected using consecutive sampling. Data analyzed using Structural Equation Modeling-Partial Least Squares. Result and Discussion: Inpatient service quality significantly affected patient satisfaction (β = 0.798; p < 0.001) and intention to recommend (β = 0.316; p < 0.001), but not patient loyalty (β = 0.059; p = 0.392). Patient satisfaction significantly influenced patient loyalty (β = 0.687; p < 0.001), while patient loyalty significantly influenced intention to recommend (β = 0.588; p < 0.001). Service quality also had significant indirect effects on patient loyalty through satisfaction (β = 0.548; p < 0.001) and on intention to recommend through satisfaction and loyalty (β = 0.357; p < 0.001). Conclusions: Inpatient service quality significantly affects patient satisfaction and intention to recommend, while patient satisfaction and loyalty mediate the relationship between service quality and recommendation intention